The art of sinning eaudiobook - Jeffries, Sabrina (Sinful Suitors, 2015)
American artist Jeremy Keane refuses to return home and take over his father's business. He'd much rather sample bevvies of beauties abroad, in search of a model for the provocative masterpiece he's driven to paint. When he meets Lady Yvette Barlow at a London wedding, he realizes she's perfect for his work—and determines to capture the young heiress's defiant spirit and breathtaking sensuality on canvas. No stranger to scandal, Yvette agrees to be Keane's subject—in exchange for his help gaining entry to the city's brothels he knows intimately, so she can track a missing woman and solve a family mystery. But when their practical partnership leads to lessons in the art of sinning, can they find a bold and lasting love? Contains mature themes.